2018
DOI: 10.18280/ijht.360105
|View full text |Cite
|
Sign up to set email alerts
|

Study on critical speed of rotation in the multistage high speed centrifugal pumps rotors

Abstract: Apart from hydraulic performance, the critical rotate speed in wet operating condition (the liquid lubricant state) is an important parameter in the designing of the multistage high speed centrifugal pumps rotors. In this paper, the finite element dynamic model of the rotor in dry state (without lubricate) is analysed by the lubricant fluid applied to the disk and cylinder parts, and a resistance equation of the influence of the fluid is proposed based on the analysis. This resistance is then coupled into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The oil in the crankcase is cooled down through the oil cooler, which is cooled by fresh water in its turn, installed in the territory of MCPS, and then comes back to the main oil tank. Practice shows that the company bears significant operating costs when servicing this system [9][10].…”
Section: Methodsmentioning
confidence: 99%
“…The oil in the crankcase is cooled down through the oil cooler, which is cooled by fresh water in its turn, installed in the territory of MCPS, and then comes back to the main oil tank. Practice shows that the company bears significant operating costs when servicing this system [9][10].…”
Section: Methodsmentioning
confidence: 99%
“…Empirical equations are established and studied by many previous researchers including Stodola [9], Cordier [10], Rodgers [11], and Wiesner [12]. Rodgers and Sapiro carried out the detailed parametric study on compressor performance and correlated the efficiency of the single stage centrifugal compressor with four major parameters: inlet specific speed, impeller tip diameter, inducer tip relative Mach number, and exit discharge Mach number [13]…”
Section: Methods Of the Velocity Trianglesmentioning
confidence: 99%
“…. For centrifugal compressor impellers, this loss coefficient includes several contributions: The blade loading loss is developed due to the negative gradient of velocity in the boundary layer and the empirical correlation is computed by Coppage[12].…”
mentioning
confidence: 99%
“…He et al 15 analyzed the natural vibration and critical speeds of the rotor of a multistage centrifugal pump with different support stiffnesses and found that the first and second critical speeds were greatly affected by the support stiffness. Tian et al 16 found that support stiffness and fluid action had an important impact on the critical speed of the multistage centrifugal pump rotor. Ashri et al 17 studied the natural frequencies and mode shapes of a centrifugal pump impeller with the finite element method and found that the impeller thickness had a great influence on the natural frequency.…”
Section: Introductionmentioning
confidence: 99%